Perubahan Pernikahan Adat Jawa Di Kecamatan Patallassang, Kabupaten Gowa - Syukur, Muhammad; Aurelia, Firzah (Rayhan Intermedia, 2024)
The culture of the Javanese people in the wedding process experiences cultural changes due to the many cultural elements originating from other tribes that are included in this traditional Javanese wedding tradition. This cultural shift was caused by various factors so that traditional Javanese weddings were mixed with native Sulawesi culture. There are various rituals that are very long and also take a long time in traditional Javanese weddings. The type of research used in conducting this research is descriptive research using qualitative data. The stages of marriage consist of proposal, preparation, pre-wedding ceremony, wedding ceremony and reception. The Bugis-Makassar and Javanese tribes who live side by side are certainly not free from social interaction. With this form of interaction between tribes, something called acculturation arises. The impact of this change then has positive and negative impacts on society. Starting from the notoni process to the reception, all of these are processes that must be gone through in carrying out a Javanese traditional wedding. The acculturation of Bugis-Makassar tribal culture with Javanese in marriage customs has resulted in Javanese traditional culture being influenced by Bugis-Makassar customs, which are the local and majority community.